Complete RNA editing of unspliced and dicistronic transcripts of the intron-containing reading frame IRF170 from maize chloroplasts. - Ruf, S (1994)
The maize plastome harbors within the rps4-rps14 gene cluster the reading frame IRF170, which is interrupted by two introns. Although the function of the encoded peptide of 170 amino acids is not known, the conservation of IRF170 homologs in other plastomes is a strong indication that IRF170 is a functional gene. Amplification and sequence analyses of IRF170 specific cDNAs reveals two C-to-U editing events occurring within each of the first two exons. This situation allows an analysis of the temporal order between editing and splicing of a chloroplast transcript. By using intron-specific primer combinations, cDNAs derived from partially or even unspliced IRF170 transcripts could be amplified which in all cases showed complete editing. Complete editing was also observed with a cDNA derived from a transcript in which the proximal rps4 and the 5' half of IRF170-encoded sequences were still linked. This demonstrates that editing of the IRF170 transcript is an early processing step preceding both splicing and cleavage to monocistronic mRNA.